SYNTHESIS OF SILICA NANOPARTICLES FROM SUGARCANE WASTE: PRECIPITATION-BASED SIZE CONTROL AND CHARACTERIZATION - Sulaiman, Mustapha; Durumin Iya, Naseer Inuwa; Aliyu, Mamudu (FUDMA JOURNAL OF SCIENCES, 2024)
Sugarcane waste, a byproduct of sugar production, poses significant environmental challenges through releasing harmful gases that contribute to air pollution and greenhouse gas emissions. This work presents the utilization of sugarcane waste to synthesize silica nanoparticles using the extraction-precipitation method. Fourier Transform Infrared (FT-IR) was used to identify the particles, and a Scanning Electron Microscope (SEM) was used to assess their size. By extracting silica from the waste material using sodium hydroxide and lowering the pH to achieve the precipitate, smaller-sized silica nanoparticles were produced. On the other hand, the silicate solution was again treated with sodium hydroxide to increase its size before the pH was lowered and the resulting precipitate was heated to a higher temperature. This also reduced the hydroxyl group content that is present due to silanol vibration. Previous studies have revealed the potential of sodium hydroxide addition for silica particle increment using the Stober method. We reported here an unprecedented increase in silica particle size with the aid of sodium hydroxide as a catalyst through a greener technique, the extraction-precipitation method.